Study on the Taxation of the Income Obtained From the Cryptocurrency Transfer - Cernușca, Lucian; Gomoi , Bogdan Cosmin; Bilți , Raluca Simina; Almași , Robert Cristian (Journal of Legal Studies, 2020)
This article discusses a number of conceptual and practical issues regarding the taxation of the income coming out from the transfer of virtual currency. The individuals who earn constant money from cryptocurrencies (over 600 lei per year) have the obligation to report their income yearly and to pay the income tax and the health insurance contributions in certain situations. According to the provisions of the Tax Code, the gains from cryptocurrency transfers will fall into the category of the taxable income from other sources. For individuals, this income will be declared through the Single Taxation Statement during the year following the year of its realization. Specifically, the earnings from cryptocurrencies in 2019 will be declared in 2020. As long as an individual keeps his income from cryptocurrencies in the form of cryptocurrencies, without actually using them, he is not obliged to declare them and pay the income tax and the Social health insurance contribution for them.